The polar phase of Li2Ge4O9 at 298, 150 and 90 K. (11th November 2013) - Redhammer, Günther J.; Tippelt, Gerold
Abstract : Dilithium tetragermanate is orthorhombic, space group P 21 ca, at 298 K, and is thus in a polar and probably a ferroelectric state. The structure contains two independent Li, four Ge and nine O atoms, all on general positions with site symmetry 1. Three tetrahedrally coordinated Ge positions form crumpled crankshaft‐like chains, forming sheets within the ac plane, and these are interconnected by the fourth, octahedrally coordinated, Ge sites along the b direction. The GeO4 tetrahedra and GeO6 octahedra form a three‐dimensional framework containing two different cavities, hosting the two 4+1‐coordinated Li sites. Cooling to 90 K does not alter the space‐group symmetry; the tetrahedral chains behave as a rigid unit and changes occur mainly within the Li coordination spheres.